PENGARUH SISTEM INFORMASI AKUNTANSI (SIA) TERHADAP KINERJA KEUANGAN PADA USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI KECAMATAN BENGKALIS - Rosa, Selvia; Zulyana, Siti; Mawaddah, Arifah (Jurnal Profiet, 2024)
This research aims to analyze the impact of Accounting Information Systems (AIS) on the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in Bengkalis District. The method used is quantitative with data collection through questionnaires distributed to MSME actors in the area. Data analysis was performed using simple linear regression to measure the extent to which AIS influences financial performance. The results of the study show that AIS has a significant but limited impact on the financial performance of MSMEs in the Bengkalis District. Quantitatively, the AIS variable affects the financial performance variable of MSMEs by 32%. This means that 68% of the variation in MSME financial performance is influenced by other variables not included in this research model. These findings indicate that although AIS is important, other factors such as operational management, marketing strategy, and economic conditions also play a significant role in determining the financial performance of MSMEs. This research contributes to the literature on the role of AIS in improving the financial performance of MSMEs and can serve as a reference for MSME owners, academics, and policymakers to consider other aspects that also significantly impact financial performance. Future research is expected to identify additional variables that influence the financial performance of MSMEs more comprehensively. Keywords: Financial Performance, MSMEs, Accounting Information Systems